The importance of evolution in the development and course of rheumatoid arthritis (2014)
Rheumatoid arthritis (RA) is a complex autoimmune disease of recent evolutionary origin. Genetic drift determines diverse polymorphisms implicated in the susceptibility to RA including the major histocompatibility complex (MHC) class II genes in the so-called shared epitope. These genes originated after the divergence between Homo and Pan from their common ancestry Ardipithecus ramidus about 5 million years ago. Natural selection determined the particular changes in the legs (bipedal position), hands, neck, brain and eusociality in humans which influence the clinical presentation of RA. In this article, we hypothesized that the origin and course of RA may be explainable in the light of evolution.